How Risky Are Banks' Risk Weighted Assets? : Evidence From the Financial Crisis - Das, Sonali (IMF Working Papers; Working Paper ;, 2012)
We study how investors account for the riskiness of banks' risk-weighted assets (RWA) by examining the determinants of stock returns and market measures of risk. We find that banks with higher RWA had lower stock returns over the US and European crises. This relationship is weaker in Europe where banks can use Basel II internal risk models. For large banks, investors paid less attention to RWA and rewarded instead lower wholesale funding and better asset quality. RWA do not, in general, predict market measures of risk although there is evidence of a positive relationship before the US crisis which becomes negative afterwards.